2000
DOI: 10.1042/0264-6021:3470749
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NRAMP1 from Arabidopsis thaliana in iron transport

Abstract: Nramp genes code for a widely distributed class of proteins involved in a variety of processes, ranging from the control of susceptibility to bacterial infection in mammalian cells and taste behaviour in Drosophila to manganese uptake in yeast. Some of the NRAMP proteins in mammals and in yeast are capable of transporting metal ions, including iron. In plants, iron transport was shown to require a reduction/Fe(II) transport system. In Arabidopsis thaliana this process involves the IRT1 and Fro2 genes. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
296
2
7

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(316 citation statements)
references
References 30 publications
9
296
2
7
Order By: Relevance
“…From primary sequence analysis, it was suggested that NRAMP1 from Arabidopsis may be plastid localized (Curie et al, 2000), and our sequence analysis of NRAMP6 using ARAMEMNON (Schwacke et al, 2003) indicates that this protein may be localized to the chloroplast, and PSORT (Nakai and Kanehisa, 1991) predicts thylakoid targeting (score 5 0.964). However, members of the NRAMP family show pH and protoncoupled activity dependent upon membrane potential (Gunshin et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From primary sequence analysis, it was suggested that NRAMP1 from Arabidopsis may be plastid localized (Curie et al, 2000), and our sequence analysis of NRAMP6 using ARAMEMNON (Schwacke et al, 2003) indicates that this protein may be localized to the chloroplast, and PSORT (Nakai and Kanehisa, 1991) predicts thylakoid targeting (score 5 0.964). However, members of the NRAMP family show pH and protoncoupled activity dependent upon membrane potential (Gunshin et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Two Arabidopsis NRAMP genes complement both iron and manganese uptake mutants in yeast (Curie et al, 2000;Guerinot, 2000;Thomine et al, 2000), and expression of a mammalian NRAMP gene in frog oocytes confers iron, copper, zinc, cadmium, manganese, and cobalt transport equally (Gunshin et al, 1997). Similarly, expression in yeast of several ZIP/IRT genes rescues not only iron and zinc uptake mutants but also manganese uptake mutants, and the uptake can be inhibited by cadmium and copper, indicating these metals might also be transport substrates (Grotz et al, 1998;Korshunova et al, 1999;Ramesh et al, 2003).…”
mentioning
confidence: 99%
“…The primary biological function of A. thaliana NRAMP transporters appears to be in Fe homeostasis. When expressed in yeast, AtNRAMPl, AtNRAMP3 and AtNRAMP4 can mediate the uptake of Fe, Mn and Cd [60]. In planta, AtNRAMP3 and AtNRAMP4 mediate the remobilization of Fe from vacuolar stores, and their expression is upregulated under Fe starvation [5,42].…”
Section: Nramp Transportersmentioning
confidence: 99%
“…Following transportation into root cells, iron is chelated by citrate or nicotianamine and distributed to the shoots (Stephan and Scholz, 1993;Briat et al, 2007). Various transporters such as YSLs, NRAMPs and VIT1 are used to distribute iron in plants (Curie et al, 2000(Curie et al, , 2009Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%